Anharmonic lattice dynamics of Te and its counter-intuitive strain dependent lattice thermal conductivity. Issue 20 (30th April 2019) - Li, Shasha; Ma, Jie; Pei, Yanzhong; Chen, Yue
Abstract : The lattice thermal conductivity of Te is found to show counter-intuitive strain dependence under uniaxial strains. Abstract : The anharmonic lattice dynamics of Te is studied based on perturbation theory using the third-order anharmonic force constants. The low lattice thermal conductivity of Te at high temperature is related to its low acoustic phonon lifetimes. In contrast to the expectation that the lattice thermal conductivity increases under compression, we find that it shows a counter-intuitive strain dependence in Te. The lattice thermal conductivity along the Te atomic chain is shown to decrease unexpectedly when a uniaxial compressive strain is applied in this direction. The lattice thermal conductivity along directions perpendicular to the Te atomic chain also shows an abnormal strain dependence. The lattice thermal conductivity under strain is analyzed based on the phonon lifetime and group velocity. Moreover, the variation of bond lengths under uniaxial strains is also discussed to provide further insight into the thermal transport behavior.